The Proof of the Truthful in Transcendental Philosophy - hamid Parsania (حکمت اسرا)
During the course of the history of Islamic philosophy, the Proof of the Truthful (burhÁn e ÒiddÐqÐn) underwent changes in the third stage of its growth where it was affected by the fundaments of Transcendental Philosophy. This article follows the development of this Proof during the last four centuries and surveys the variegated expositions that it has had in this period.